2022
DOI: 10.47307/gmc.2022.130.s1.34
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Developmental Delay in the First 5 Years of Children

Abstract: Developmental delay is quite common in children, but the detection of this disorder is still low. About 52.9 million children younger than five years were diagnosed with developmental delays worldwide. This study aimed to analyze the determinant of developmental delay in the first five years of children in Indonesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The current findings showed an increased risk of SDD in communication domain for children born to mothers over 35 years, consistent with Sanjaya et al ’s research. 35 Advanced maternal age’s impact on maternal and fetal health was highlighted in the study by Mehari et al . 40 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current findings showed an increased risk of SDD in communication domain for children born to mothers over 35 years, consistent with Sanjaya et al ’s research. 35 Advanced maternal age’s impact on maternal and fetal health was highlighted in the study by Mehari et al . 40 …”
Section: Discussionmentioning
confidence: 99%
“…The current findings showed an increased risk of SDD in communication domain for children born to mothers over 35 years, consistent with Sanjaya et al's research. 35 Advanced maternal age's impact on maternal and fetal health was highlighted in the study by Mehari et al 40 Immigrant children from various nationalities had a higher likelihood of SDDs in all domains except fine motor. A study conducted in Singapore also found that minority ethnicity was associated with positive developmental screening outcomes in gross motor.…”
Section: Open Accessmentioning
confidence: 97%